LITERATUR REVIEW AUGMENTED REALITY SEBAGAI MEDIA PROMOSI DENGAN METODE MARKER BASED TRACKING - Fauzan, Mohamad Nurkamal; Kautsar, Muhammad (NUANSA INFORMATIKA, 2023)
Augmented Reality (AR) is a technology that combines real-world objects with virtual or digital objects in a real-world setting. Real and virtual objects are merged using appropriate technologies, and interactions occur through specific tools and devices. The use of AR in solving everyday life problems has expanded across various fields, including advertising. Brochures are one of the print media that can be used for advertising and integrated with augmented reality technology. The use of augmented reality technology in brochures can provide a new solution in brochure creation, making them more creative, engaging, and accessible to a wider audience. It offers complete, clear, and easily accessible information compared to traditional brochures